상급종합병원 병동담당약사 업무 현황 및 의료인의 인식과 기대 분석 - 김정은; 백시진; 최나예; 전수정; 남궁형욱; 이정화; 김은경; 이주연; Kim, Jeongun; Baek, Sijin; Choi, Nayae; Jeon, Sujeong; et al. (한국임상약학회지, 2022)
Background and objective: The Seoul National University Bundang Hospital (SNUBH) implemented ward-based clinical pharmacy system with designated pharmacists in 10 general wards. Designated pharmacists conduct inpatient medication review, medication intervention, and medication consultation, and provide drug information for health care providers. This study aimed to evaluate the clinical pharmacy services and to examine the perception and expectations of health care providers on the services provided by the designated pharmacists in general wards. Methods: A survey was constructed to include questions on the health care providers' recognition, satisfaction, and perceived needs of designated pharmacists. We determined the frequency and type of interventions of ward pharmacist and their acceptance rate through a retrospective observational study using electronic medical records. Results: A total of 59 health care providers responded the questionnaire and 79.7% of the respondents reported moderate to high levels of satisfaction. Satisfaction with the services was positively associated with clinical interventions and nutrition support team (81.4%). Of 59 respondents, 88.1% agreed that preventing drug-related problems by designated pharmacists' activities were effective. The most common interventions included inadequate dosage (27.4%), omission and additional prescription (14.6%) and inadequate drug form (9.6%). The acceptance rate of intervention was 91.5%, and 151 potentially serious risks and 523 significant risks were prevented by the intervention. Conclusion: Positive results were confirmed in the awareness, satisfaction, and perceived needs of the health care providers for designated pharmacists. Expansion of the ward-based clinical pharmacy system with designated pharmacists to other wards may be considered.